2007
DOI: 10.1080/07357900601130664
|View full text |Cite
|
Sign up to set email alerts
|

Employment and Cancer: Findings from a Longitudinal Study of Breast and Prostate Cancer Survivors

Abstract: We discuss how cancer affected the employment of almost 800 employed patients who participated in a longitudinal study. The greatest reduction in patients' labor supply (defined as employment and weekly hours worked) was observed 6 months following diagnosis. At 12 and 18 months following diagnosis, many patients returned to work. Based on these and other findings related to patients' employment situations, we suggest 4 areas for future research: 1) collection of employment information in cancer studies; 2) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
123
2
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(146 citation statements)
references
References 26 publications
6
123
2
15
Order By: Relevance
“…In addition to these more holistic effects, earning declines may also result in a decrease in general welfare that may extend to the family as a whole if the breadwinner is diagnosed with cancer. Potential changes in earnings have not been as extensively studied as employment changes, but our results appear overall to be somewhat higher than previously estimated [4,25,37]. This may be due to our unselected cancer cohort, including also survivors of understudied cancer forms.…”
Section: Discussioncontrasting
confidence: 52%
“…In addition to these more holistic effects, earning declines may also result in a decrease in general welfare that may extend to the family as a whole if the breadwinner is diagnosed with cancer. Potential changes in earnings have not been as extensively studied as employment changes, but our results appear overall to be somewhat higher than previously estimated [4,25,37]. This may be due to our unselected cancer cohort, including also survivors of understudied cancer forms.…”
Section: Discussioncontrasting
confidence: 52%
“…There are numerous studies of breast cancer's impact on employment, motivated by the fact that with screening and earlier detection, working age women are more likely to be diagnosed with and treated for the disease. One study found that women with breast cancer were 17 percentage points less likely to be employed than women in a non-cancer control group six months following diagnosis, but by 12 and 18 months following diagnosis, their likelihood of employment was not statistically different (Bradley et al, 2007). Recent studies of breast cancer and employment also find evidence that breast cancer does not lead to substantial longer-term declines in employment; examining over 1,000 initially-employed women diagnosed with breast cancer, Mujahid et al (2011) report that approximately 90% were employed nine months following diagnosis, although non-employment rates were higher for Latina women than for white women.…”
Section: Application To Breast Cancermentioning
confidence: 99%
“…For example, Hassett et al (2009) reported return to work rates of 93% among over 3,200 employed and insured women, but those who received chemotherapy were more likely to go on disability, stop working, or retire relative to women who did not receive chemotherapy. The effects of chemotherapy can continue for several months or even years following the completion of treatment (Bradley et al, 2007;Johnsson et al, 2011;Hassett et al, 2009). …”
Section: Application To Breast Cancermentioning
confidence: 99%
“…8 Those who do return to work, report problems in their ability to perform mental tasks such as concentrating, learning new things and multi-tasking. 9,10 To date, except for two studies, 7,8 most of the evidence for the effect of cognitive impairments on the quality of working life come from self-report studies. [10][11][12][13] Thus, it is possible that breast cancer patients are sensitive to subtle changes in cognitive function that current neuropsychological test employed are unable to detect 1 or that neuropsychological tests may not equate with everyday cognitive problems.…”
Section: Introductionmentioning
confidence: 99%